MILITARY ORGANIZATIONAL CULTURE AND KNOWLEDGE MANAGEMENT IN A SYSTEMATIC LITERATURE REVIEW - Parlindungan, Parlindungan; Rofaida, Rofi; Senen, Syamsul Hadi (Business Education Program of Universitas Pendidikan Indonesia, 2024)
AbstractStudy this study and analyze in a way comprehensive role culture organization military and management knowledge in organization military nor police. Study this use method systematic literature review (SLR), study this serve understanding deep about how culture organization in environment military and police influence and interact with practice management knowledge. Research result show that culture organization military and police, characterized by discipline high, loyalty strong, working the same team, leadership firm, and loyal against the country, plays role crucial in effectiveness and efficiency management knowledge. This is reflected in behavior work innovative, making decisions, improvement productivity, as well subtraction error in operation military and enforcement law. However, challenges like lack of openness in share knowledge and potential restrictions creativity and innovation because strict discipline and authority are also identified. Study this offer recommendation to develop management strategies more knowledge comprehensive and effective, in line with culture organization military and police. Study this give contribution important in understand how culture organization military and police can optimized to increase management knowledge, support innovation, and facing challenge complex operations.